Improved antimicrobial activity of silica–Cu using a heteropolyacid and different precursors by sol–gel: synthesis and characterization - Arreche, Romina (2015)
Antimicrobial paintings incorporate biocides in low concentrations to avoid the proliferation of fungi and bacteria inside urban buildings. This study is focused on evaluating the antifungal activity of copper (II) supported on a silica matrix and as counter cation of a heteropolyacid, obtained from the sol-gel method using various catalysts; against two fungal isolates. The fungi used in this evaluation were isolated by routine microbiological techniques, two isolates, Alternaria alternata and Chaetomium globosum were used. In all cases fungi were selected for their ability to grow on the paint films and their negative impact on human health were taken into account. First, were prepared silicas, using tetraethylorthosilicate and methyl trimethoxysilane as precursors and acetic acid, hydrochloric acid, and catalysts while the hydrolysis reaction of the alkoxide. The effect of addition of copper (II) in the form of copper nitrate was studied. With respect to the morphology of the silica, most of which are similar, between pure and modified silica, in all cases. Once the stage of synthesis and characterization of silicas proposals were selected six of them to evaluate their antifungal activity by the plaque inhibition test against both fungi of interest (Alternaria alternata and Chaetomium globosum), and the percent inhibition was determined in each case. Tested Cu-solids were shown to have a higher antifungal activity completely inhibit the growth of both fungi with lower concentrations relative to its target. The work consummate in a preliminary way, guide the selection of a suitable organic biocide from a list of possible antifungal agents.